Level and Trend of Writing Sequences: A Review and Meta-Analysis of Writing Interventions for Students With Disabilities. (January 2020) - Datchuk, Shawn M.; Wagner, Kyle; Hier, Bridget O.
We examined effects of intervention on the level and trend of text-writing sequences of students with disabilities and writing difficulties, in addition to potential moderating effects related to student demographics (i.e., disability status, age, gender, and race) and writing task (i.e., sentence, essay, and narrative). We reviewed 18 single-case experimental design studies with a total of 96 students and subsequently meta-analyzed 15 of these studies with a total of 79 students using mixed-effects linear regression and an information-theoretic ranking of competing models. Results indicate that writing interventions, including direct instruction and self-regulated strategy development, produced gradual improvement in the trend of correct writing sequences per minute. Older students produced higher levels of writing sequences, but younger students showed steeper trends during intervention. Furthermore, students had higher levels of writing fluency on sentence-writing tasks than on discourse-writing tasks (narratives and essays).